2021
DOI: 10.1099/mgen.0.000623
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gdpP gene are a clinically relevant mechanism for β-lactam resistance in meticillin-resistant Staphylococcus aureus lacking mec determinants

Abstract: In Staphylococcus aureus , resistance to β-lactamase stable β-lactam antibiotics is mediated by the penicillinbinding protein 2a, encoded by mecA or by its homologues mecB or mecC. However, a substantial number of meticillin-resistant isolates lack known mec genes and, thus, are called meticillin resistant lacking mec (MRLM). This study aims to identify the genetic mechanisms underlying the MRLM phenotype. A total of 141 MRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 71 publications
3
41
0
1
Order By: Relevance
“…Two of the most prevalent BORSA sequence types, ST97 ( n = 5) and ST398 ( n = 5), have historically been contextualized as livestock-associated MRSA ( 34 38 ), though recent reports from France and the United States have described ST398 isolates of our predominating spa type, t1451, as human bloodstream infection (BSI)- and hospital-associated MSSA isolates ( 39 41 ), reflecting the demographics of our cohort. Moreover, a German study also found ST398 to be the third-most-common sequence type among their BORSA isolates of clinical origin ( 42 ). Yet, to the best of our knowledge, only five ST97 isolates have previously been annotated as BORSA ( 20 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the most prevalent BORSA sequence types, ST97 ( n = 5) and ST398 ( n = 5), have historically been contextualized as livestock-associated MRSA ( 34 38 ), though recent reports from France and the United States have described ST398 isolates of our predominating spa type, t1451, as human bloodstream infection (BSI)- and hospital-associated MSSA isolates ( 39 41 ), reflecting the demographics of our cohort. Moreover, a German study also found ST398 to be the third-most-common sequence type among their BORSA isolates of clinical origin ( 42 ). Yet, to the best of our knowledge, only five ST97 isolates have previously been annotated as BORSA ( 20 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…MRSA is one of the most prominent agents contributing to the significant global antimicrobial resistance burden today (3). However, in recent years, the presence of β-lactam resistance in S. aureus strains without mecA have been reported (10, 22, 23). In previous studies, we have demonstrated the ability of PBP4 to mediate high-level β-lactam resistance via protein overexpression due to promoter-associated mutations in non- mecA strains (7, 17).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted that increased CDA concentrations promote tolerance to β-lactam antibiotics and allow cell wall restructuring (8,11). Furthermore, a growing number of contemporary clinical surveillance studies have identified mutations in gdpP among β-lactam resistant or non-susceptible natural isolates of S. aureus (12)(13)(14)(15). Since many of these mutations have been either shown (8) or are predicted to attenuate the function of GdpP, causing increased CDA concentrations in cells, these findings underscored the clinical importance of CDA and highlighted the importance of accurate determination of its concentrations for both basic and clinical research settings.…”
Section: Main Textmentioning
confidence: 99%